PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA PELAJARAN BAHASA INDONESIA KELAS 3 - Nurhidayat, Asep (PRODI PGSD UNIVERSITAS PGRI DELTA, 2023)
Reading is one of the most important language skills in addition to other language skills. Because reading is a means to learn about other desired worlds so that humans can expand their knowledge, have fun, and explore written messages only by reading. However, reading is not an easy task. Reading is a process that can be developed by using approaches, techniques, strategies, and methods that are in accordance with the purpose of reading. Reading comprehension is an activity that aims to obtain in-depth information and understanding of what is read. The importance of reading comprehension for students is to gain a full understanding of logical arguments, students can determine the main idea in the reading, students can read the entire content of the reading carefully, and students can restate the content of the reading using their own sentences. One of the learning models that has a creative way of learning for students is the Problem Based Learning (PBL) learning model. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on reading comprehension skills in Indonesian language lessons for grade 3 students of SDN 138 Gegerkalong Girang, Bandung City. This research uses quantitative and qualitative approaches, with the type of research is classroom action research (PTK). Data collection used in this research are (1) observation, (2) test, and (3) documentation. The stages carried out in this study are: (1) preparation stage; (2) implementation stage; (3) data processing stage; and (4) reporting stage, compiling data analysis and research conclusions in the form of a final report.